A New Species of Ligyrocoris Stal With a Key to the Northeastern Species (Hemiptera:Lygaeidae) - Merrill H. Sweet (Psyche: A Journal of Entomology)
In the course of current work upon the biology and ecology of the Rhyparochrominae of New England, a new species of Ligyrocoris was discovered. The species runs in Barber's (1921) key to the couplet separating diffusus (Uhler) from sylvestris (L.), but is distinct from either species. While the new species is closely related to these species, it is also quite close to L. depictus which is separated out in a different part of Barber's key.